2019
DOI: 10.1093/jn/nxz108
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity is Associated with Higher Adiposity among US Schoolchildren Ages 10–15 Years: The Healthy Communities Study

Abstract: Background Limited research exists on the relationship between food insecurity and children's adiposity and diet and how it varies by demographic characteristics in the United States. Objective The aim of this study was to assess the relationship between household food insecurity and child adiposity-related outcomes, measured as BMI (kg/m2) z score (BMI-z), weight status, and waist circumference, and diet outcomes, and examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…Youth from lower SES families are also more likely to experience food insecurity [56][57][58]. Food security can be categorized into one of four ranges: very low, low, marginal, and high food security [59].…”
Section: Socioecological Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth from lower SES families are also more likely to experience food insecurity [56][57][58]. Food security can be categorized into one of four ranges: very low, low, marginal, and high food security [59].…”
Section: Socioecological Influencesmentioning
confidence: 99%
“…Most recent estimates have shown a continuous decline in the percentage of food insecure households since 2011 [57]. While low-income families and households with children, in particular non-Hispanic black and Hispanic households, remain at percentages above the national average [57], this shift in prevalence is promising given that household food insecurity is related to overweight and obesity in youth [56,58,60,61].…”
Section: Socioecological Influencesmentioning
confidence: 99%
“…This study has identified male sex, low SES, adolescence, and high BMI as factors associated with an increased risk of low folate and/or cobalamin serum concentrations. There is growing evidence regarding the complex and seemingly paradoxical relationship between pediatric obesity and food insecurity [ 49 , 50 , 51 ], defined as “limited or uncertain availability of nutritionally adequate and safe foods or limited or uncertain ability to acquire acceptable foods in socially acceptable ways” [ 52 ]. Household food insecurity contributes to unhealthy diet-related behaviors, increasing the risk of nutritional inadequacy and adiposity, particularly among older children [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy diets, excessive screen time, and inadequate moderate-to-vigorous physical activity are well-established obesity risk factors. Lack of access to healthy food or household food insecurity contribute to unhealthy diets [ 4 ]. The prevention of childhood obesity can involve primary, secondary, and tertiary approaches to promote healthy behaviors in all children and those with the highest risk of developing obesity, as well as children with obesity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%